Developing Materials of an EFL Reading Courseware Prototype for 8th Grade Students of Junior High School - Hendryanti, Retno (2006)
This study examines the processes involved in developing a prototype of an EFL reading courseware for the 8th grade of junior high school, the students' and teacher's responses towards the courseware, and the effectiveness of the prototype.The participants of this study are one acceleration class of 8th grade students and an English teacher of a junior high school in Bandung. Thirty six students were involved in needs analysis stage and 10 students and 1 teacher were involved in evaluation stage. These participants were selected purposively. There are five main instruments used in this study, i.e. (1) questionnaire for needs analysis and courseware evaluation, (2) interview guidelines, (3) observational sheets, (4) learning materials in the form of the prototype courseware, and (5) tests, which include a pre-test and a post-test. Findings from the questionnaires, interviews, and observational sheets are analyzed descriptively. Meanwhile, scores from the pre-test and post-test are analyzed using the matched t-test.It is found that there are five steps in preparing the reading materials: (1) deciding the overall purpose, (2) selecting texts and tasks, (3) identifying linguistic elements, (4) sequencing and integrating texts and tasks, and (5) linking reading to other skills. Meanwhile, the production of the courseware includes three steps: (1) developing the operational model of the courseware, (2) developing the storyboard, and (3) translating the operational model and the storyboard into a machine language. It is also found that both the students and the teacher give positive responses. Finally, the pre-experimental study on courseware's effectiveness shows that the courseware appears to increase the students' reading comprehension.It can be concluded that effective courseware production requires systematic plans and steps that are theoretically sound and a solid teamwork of several experts so that the users will obtain meaningful learning experiences. Despite this high requirement, the development of reading courseware as supplementary materials for the textbooks is worthy since the reading courseware received positive responses from both the students and teacher and was preliminary proven effective in improving the students' reading skills. The positive responses and the courseware's effectiveness perhaps are due to the nature of multimedia which provides interactivity between the users and the computer, incorporates various modes of inputs, and accommodates the users' learning preferences. Further, although the focus of the courseware is reading, other language elements, such as speech, can also be incorporated to support the reading skill. This is in accordance with the nature of multimedia itself, which support learning through various modes of inputs.Further, it is recommended that further studies develop courseware for other language skills, try out the courseware to a larger number of participants by integrating it with the syllabus used in class, and measure the courseware's effectiveness through true experimental design so that the result can be generalized. It is also recommended that teachers use the courseware to promote self-directed learning so that students may learn to be responsible for their own learning.